(untitled) (Research, Society and Development, 2021)
Records of the Pleistocene megafauna are well documented in Brazil. Among the many representatives of the megafauna, representatives of the Mylodontidae and Megatheriidae (i.e., giant sloths of the Quartenary) Evidence suggests that these representatives were terrestrial animals and somehow “built” natural cavities. These cavities are called paleoburrows and have great paleontological importance as they contain ichnofossiliferous records (e.g., claw marks) that provide evidence about the biology of the building agents. Although these structures are known in Rio Grande do Sul and Southeastern Brazil, Paraná and the northern plateau of Santa Catarina, records of these structures are non-existent. . In this sense, the objective of this study was to describe the patterns of tunnels and the ichnofossils produced by burrowers animals from megafauna in the municipalities of União da Vitória and Porto União, southern Brazil. The “Snowball sampling” method was used to find the paleotocas, later measurements such as height and width were obtained using metric materials. The trace fossils were measured using an ordinary ruler. Thirteen free or partially obstructed paleoburrows and six crotovins were found, built in sandstones of the Botucatu Formation. Four different tunnel morphologies were identified and inside, five different types of ichnofossils attributed to scratch marks were identified. Due to their similar characteristics, some marks have been attributed to individuals of Mylodontidae.